Effects of pendant side groups on the properties of the silicon-containing arylacetylene resins with 2, 5-diphenyl-[1, 3, 4]-oxadiazole moieties. Issue 32 (1st June 2021) - Ma, Manping; Liu, Xiaotian; Li, Chuan; Qiao, Zhiyao; Yuan, Qiaolong; Huang, Farong
Abstract : Silicon-containing arylacetylene resins with rigid conjugated structures in the main chain often exhibit poor processability and low mechanical properties. Abstract : Silicon-containing arylacetylene resins with rigid conjugated structures in the main chain often exhibit poor processability. A strategy of improving the processability by destroying the molecular structure symmetry using side aromatic groups was proposed, and the effects of the side groups was further explored. Two novel structural resins with side aromatic phenyl and phenylacetylene groups (PODSA-2P-MM and PODSA-2E-MM) were synthesized by Grignard reaction. The side aromatic groups strongly interfere with the regular arrangement of the main chains, and the crystallinities of the resins decrease as compared with PODSA-MM resin without side aromatic groups. Due to the influence of the side aromatic groups, the novel resins exhibit good processability, low exothermic enthalpy, high modulus and good heat resistance.